Um dos novos rostos da histeria: os sintomas anoréxicos como resposta ao discurso do capitalismo - Ernesto Andres Anzalone Vazquez (2011)
Although currently there seems to be certain disinterest in hysteria, still persists its undeniable contribution to the history of psychoanalysis, which arises precisely from the Freud efforts to decipher the hysterical symptom. However, what can be nowadays the hysteria contribution? Today, sexual repression became, after the sexual liberation of the late twentieth century, in a sexual overexposure. The contemporary master shows us, through science, a multitude of products, objects that try to satisfy us. This is a proposal for full jouissance that escapes from the lack of jouissance in the present phallic. For the capitalist discourse there is a lack that can not be satisfied by the latest gadget, there is no lost object for the market, but an object to be produced and consumed. However, the symptom resists. We witness the emergence of mental illness "epidemics", existing pathologies "fashions". The current Psychiatry, using what appears to be an endless source of names that being more descriptive means less and less, supports the model of a university discourse stripped of particularities of the subject and of any attempt of meaning. These neo-epidemics have taken the place of the social bond currently fractured. These subjects identify their own symptoms: they are anorexic, depressed, etc.. The nomination includes a group and the consistency of their symptoms, emphasizing the universal and the not particular of them. It is not a way of hysterical identification, from desire to desire, but what could be termed as a community of jouissance. These communities have made special use of new forms of communication, especially the Internet, proliferating groups, forums, websites and chat rooms that bring together groups of people identified in specific jouissances. In this sense our interest will focus on the subject of significant growth that has been identified with the anorexic symptom. Accordingly, from the analysis of two autobiographies of individuals who nominate themselves as anorexic (Cielo Latini and Lori Gottlieb), binds the discourse that sustains their symptoms in a particular relationship with the jouissance and the Other. We look at this particular relationship, showing how some of the hysterical subjects, use anorexic symptom to demand the Other. We postulate the existence of a form of anorexia (which does not exclude other forms), that we will call "transitional," which is marked by this demand to the Other as a way to preserve their desire. Before the imposition of the capitalist discourse as a new master, as a "should" jouir, the hysteria answers from the symptom. In such cases, the anorexic symptom claims the "right" to jouissance showing from the extreme, that there is always a lack. The proposal for a universal and absolute jouissance, inevitably faces the particularity of the subject